UJI EFEK TONIKUM EKSTRAK ETANOL DAUN SAMBILOTO (Andrographis paniculata, Nees.) TERHADAP MENCIT JANTAN (Mus musculus L.) GALUR SWISS - Endrawati, Susi; Indriyani, Feni (Sistem Informasi, 2016)
The tonic is a substance that can improve our body strength. It can recover the staff our body shortly. It can also make our body stronger and can stimulates our appetite. Knowing the most effective tonic effect dose variation among ethanol extract of bitter leaf on male mice (Mus musculus L.) Swiss Strain. This study is an experimental research design with True experimental design approach Posttest Pretest with control group. The ethanol extract of bitter leaf is made with bitter leaf quote using ethanol 96% with maceration method. The provision of treatment in test animals distinguished on several variations of dosage. In preparation extracts there are 5 groups, namely: group I, II, III, IV, V treated positive control caffeine 13 mg / kg, cooking oil as a negative control, the ethanol extract at a dose of 50 mg / kg, 100 mg / kg, 200 mg / kg. Data obtained tonic effect of added time the mices ability to defend itself when direnangkan. Data were analyzed by ANOVA using SPSS 18.0 for windows followed by a test post hoc test and ED50 probit analysis to determine the most effective dose as a tonic. Ethanol extract of bitter leaf at a dose of 50 mg / kg have a tonic effect of 9.2 minutes, a dose of 100 mg / kg have a tonic effect of 13.4 minutes, and a dose of 200 mg / kg have a tonic effect 23 minutes. Results yield of ethanol extract of bitter leaf maceration 7.8% b/b. The ethanol extract of bitter leaf tested in test animals male mice (Mus muculus L.) at all doses provide a tonic effect, and the effect will increase along with increasing doses of test substance preparation.